Naming 'junk': Human non-protein coding RNA (ncRNA) gene nomenclature - Wright Mathew W; Bruford Elspeth A (Human Genomics, 2011)
Abstract Previously, the majority of the human genome was thought to be 'junk' DNA with no functional purpose. Over the past decade, the field of RNA research has rapidly expanded, with a concomitant increase in the number of non-protein coding RNA (ncRNA) genes identified in this 'junk'. Many of the encoded ncRNAs have already been shown to be essential for a variety of vital functions, and this wealth of annotated human ncRNAs requires standardised naming in order to aid effective communication. The HUGO Gene Nomenclature Committee (HGNC) is the only organisation authorised to assign standardised nomenclature to human genes. Of the 30,000 approved gene symbols currently listed in the HGNC database (http://www.genenames.org/search), the majority represent protein-coding genes; however, they also include pseudogenes, phenotypic loci and some genomic features. In recent years the list has also increased to include almost 3,000 named human ncRNA genes. HGNC is actively engaging with the RNA research community in order to provide unique symbols and names for each sequence that encodes an ncRNA. Most of the classical small ncRNA genes have now been provided with a unique nomenclature, and work on naming the long (> 200 nucleotides) non-coding RNAs (lncRNAs) is ongoing.